2013
DOI: 10.1002/rcm.6520
|View full text |Cite
|
Sign up to set email alerts
|

Collision‐induced dissociation studies of caffeine in positive electrospray ionisation mass spectrometry using six deuterated isotopomers and one N1‐ethylated homologue

Abstract: As basic CID reactions of caffeine have been elucidated in this work, the developed fragmentation scheme may serve as a valuable tool for the interpretation of ESI-CID fragmentation spectra of more complex xanthine derivatives and their respective metabolites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 35 publications
8
14
0
Order By: Relevance
“…The product ion at m/z 414.3 is associated with a neutral loss of methyl isocyanate (O=C=NCH 3 , 57 Da) which results from a reverse Diels‐Alder rearrangement in agreement with previously reported fragmentation mechanisms of caffeine; however, Bier et al suggested this species was in equilibrium with a ring‐closed analog (shown for m/z 414.3). The ring‐closed form more closely agrees with subsequent fragmentation leading, for example, to the formation of ions m/z 386.6 and 342.5.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…The product ion at m/z 414.3 is associated with a neutral loss of methyl isocyanate (O=C=NCH 3 , 57 Da) which results from a reverse Diels‐Alder rearrangement in agreement with previously reported fragmentation mechanisms of caffeine; however, Bier et al suggested this species was in equilibrium with a ring‐closed analog (shown for m/z 414.3). The ring‐closed form more closely agrees with subsequent fragmentation leading, for example, to the formation of ions m/z 386.6 and 342.5.…”
Section: Resultssupporting
confidence: 87%
“…The ion at m/z 427.3 is further dissociated to form ions at m/z 400.5 and 398.4 due to the neutral loss of hydrogen cyanide (27 Da) and methanimine (CH 3 N, 29 Da), respectively, and these product ions were confirmed through MS 3 analysis (Figure S2A, supporting information). The elimination of carbon monoxide (CO, 28 Da) from m/z 414.3 leads to the formation of m/z 386.6, as described previously . An alternative fragmentation pathway was proposed by Thevis et al in which neutral loss of CO occurred through an open‐ring form, although it is noteworthy that the monomeric analog shown in their study was unsubstituted at the N‐1 position.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations